Analisis Perubahan Morfologis Pembentukan Ta’rib dan Pembelajaran - Amrulloh, Muhammad Afif; Himmah, Ro'fat Hizmatul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2017)
The birth of a variety of new vocabulary or term in the Arabic language that originated in a foreign language is a form of a modern linguistic phenomenon that emerged at this time. The reality shows that Arabic continues to evolve following the times that certainly gives its own difficulties for speakers of the Arab nation as well as from outside the Arab nation. However, this article will discuss the changes that occur in the morphological process of Arabization. This research used the qualitative research, including the types of research studies library or library research that takes a data source in the library. While the methods used i.e. linguistic analysis methods on morphology to produce conclusions as for the basis for the formation of Arabization. The results of this research show that there is at least some form of absorption process of morphological changes in the words used in the process of Arabization, i.e. ta'rib or morfemis/afiksasi process with the form sirkumfiks, the suffix, and prefix. Some forms of these processes contribute to the understanding of the application of some rules of Arabization to ease the Arab language learners and speakers from outside the Arab nation in learning, understanding and generate new vocabulary needed in communications globally. Penelitian ini akan membahas tentang perubahan morfologis yang terjadi dalam proses arabisasi. Penelitian ini merupakan jenis penelitian kualitatif, termasuk penelitian studi pustaka atau library research yang mengambil sumber data secara kepustakaan. Metode dalam penelitian ini yaitu metode analisis kebahasaan pada morfologi untuk menghasilkan kesimpulan untuk menjadi dasar pembentukan arabisasi. Hasil dari penelitian ini menunjukkan bahwa setidaknya ada beberapa bentuk penyerapan kata dalam proses perubahan morfologis yang digunakan dalam proses ta’rib atau arabisasi, yaitu proses  morfemis/afiksasi dengan bentuk sirkumfiks, sufiks dan prefiks. Beberapa bentuk proses tersebut memberikan kontribusi terhadap pemahaman penerapan beberapa kaidah arabisasi sehingga memudahkan para pembelajar bahasa Arab dan penutur dari luar bangsa Arab dalam mempelajari, memahami dan menghasilkan kosa kata baru yang dibutuhkan dalam komunikasi secara global yang lebih luas.